Новые аспекты в исследовании свариваемости — предпосылки для технологии и обеспечения качества процесса сварки - Герольд, Х. (Автоматическая сварка, 2008)
The author report on a new concept of an integrated consideration of joinability, including all modern variations of
modern joining processes is presented. Joinability takes into account all special influences on a joint component as
affecting joint suitability in respect to material, joint capability for processing, and joint reliability for use and service.
Special selected examples explain the self-contained concept of joinability, and solutions for the preparation of production
are offered.